IMPLEMENTASI PENGELOLAAN PEMBELAJARAN â€œPARENTING CLASSâ€ DI SD MUHAMMADIYAH DHURI - Diyah Puspitarini (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2020)
This research aims to describe implementation the management of "Parenting Class" learning at SD Muhammadiyah Dhuri. The research method used is qualitative. Subject of research are parents of students. The object research using management parenting class model. Data analysis techniques used reduction, data presentation, and data verification. The result of this research is the pattern of learning management process "Parenting Class" at SD Muhammadiyah Dhuri which includes the planning, organizing, training and evaluation processes. Based on the results of the analysis, the parents and teachers were satisfied because they got new knowledge and there were changes in the parenting carried out by the parents and there were changes in the children's attitudes after the parents changed the old parenting styles.